Pandangan MUI Kabupaten Bengkalis Sholat Jama’ah Khusus Perempuan Pada Hari Raya Besar Islam Di Dusun III Simpang Ayam - Norafiza, Sri; Asriani, Weni (Sekolah Tinggi Agama Islam (STAI) Al- Kifayah Riau, 2023)
The purpose of this study was to find out the views of the Bengkalis Regency MUI regarding women's congregational prayers on holidays in Simpang Ayam Hamlet III. The research method used is a qualitative method by means of interviews. The results and discussion in this study are the history of congregational prayers, the meaning of congregational prayers specifically for women, the law of becoming an imam and the requirements to become an imam and congregation. The conclusion of this study is to know the law of praying in congregation specifically for women through the MUI of Bengkalis Regency, namely that the law is permissible as long as all makmum must also be women because if there is a makmum there is a man then the law is unlawful